Abolitionist Feminism as Prisons Close: Fighting the Racist and Misogynist Surveillance “Child Welfare” System - Michalsen, Venezia (The Prison Journal, 2019)
The global prison industrial complex was built on Black and brown women’s bodies. This economy will not voluntarily loosen its hold on the bodies that feed it. White carceral feminists traditionally encourage State punishment, while anti-carceral, intersectional feminism recognizes that it empowers an ineffective and racist system. In fact, it is built on the criminalization of women’s survival strategies, creating a “victimization to prison pipeline.” But prisons are not the root of the problem; rather, they are a manifestation of the over-policing of Black women’s bodies, poverty, and motherhood. Such State surveillance will continue unless we disrupt these powerful systems both inside and outside prisons.
Keywords: dept.soc; peer-reviewed

A Cell of One’s Own? Incarceration and Other Turning Points in Women’s Journeys to Desistance - Michalsen, Venezia (International Journal of Offender Therapy and Comparative Criminology, 2019)
Research has shown the importance of turning points in desistance from criminal behavior. Using qualitative data from a sample of 100 formerly incarcerated mothers interviewed about their criminal behavior, this article explores their descriptions of transition moments and whether and how those moments affected their criminal behavior. The findings indicate that whereas parenting emerges as a turning point, the practical difficulties of reentry may reduce the impact of mothering on women’s desistance. More self-focused turning points, such as those due to incarceration, arrest, and sobriety appeared to be particularly important to the women’s desistance. This article emphasizes the need for research into the subjective and environmental factors that affect women’s desistance behaviors.
Keywords: dept.soc; peer-reviewed

Belarus at the United Nations: An analysis of Belarus's global policy alignment following the Maidan revolution in Ukraine - Lennon, O.; Becker, A. (Demokratizatsiya, 2019)
Since the fall of the Soviet Union, Belarus has been the slowest of the countries in Eastern Europe to shake off its authoritarian past and ties with Russia. However, the Maidan revolution in Ukraine and Russia's subsequent annexation of Crimea and occupation of parts of Eastern Ukraine in 2014 might have forced Belarus's president, Aleksander Lukashenka, to start questioning the terms of this relationship. Russia's violation of Ukraine's sovereignty created a much more real possibility-and fear-that, if push came to shove, Russia would not hesitate to act similarly toward Belarus. Belarus's political choices are hard to predict: will it remain a dictatorship in Russia's shadow or will it embrace democracy and the rule of law and seek closer integration with the West? This study examines Belarus's global policy alignment from 2007 to 2017 by analyzing its voting patterns on contested issues-those on which Russia's and the U.S.'s votes diverged-at the United Nations General Assembly. While Belarus seems to have been disassociating itself from Russia on some global issues, as evidenced by its voting record at the UN General Assembly, and its democracy level increased from 2014-2016, there is insufficient evidence to believe that Belarus might in fact be aligning more with the West and moving away from Russia. While Belarus's diplomatic pendulum has increasingly swung toward the US, it has inevitably bounced back to its "home base"-Russia. © 2019 Heldref Publications. All rights reserved.
Keywords: Belarus; Crimea; Russian Federation; Ukraine; United Nations; authoritarianism; democracy; dept.soc; diplomatic relations; international relations; peer-reviewed; policy approach; sovereignty; voting behavior; ⛔ No DOI found

Principles of racial integration vs. perceptions of non-White neighborhoods: Comparing hypothetical and real neighborhood choice - Meyerhoffer, Cassi A.; Kenty-Drane, Jessica (Journal of Urban Affairs, 2019)
Using qualitative interview data, we examine the consistency of White residents' responses to questions about their preferences for the racial composition of their neighborhoods when comparing hypothetical showcards and maps of real neighborhoods in respondents' cities. This approach allows for an examination of how residents' preferences for real neighborhoods align with preferences for idealized neighborhoods and the explanations people give when describing their preferences for neighborhoods of color. Data come from qualitative interviews conducted in Buffalo, New York, and Ogden, Utah.
Keywords: Buffalo; New York [New York (STT)]; New York [United States]; Ogden; United States; Utah; data set; dept.soc; neighborhood; peer-reviewed; perception; qualitative analysis; racial disparity; racial segregation

All is quiet on the Russian front: ceasefires and the pursuit of legitimacy by self-proclaimed “republics” in Ukraine - Lennon, Olena; Adams, Gregory (Eurasian Geography and Economics, 2019)
This paper examines the pursuit of legitimacy by the self-proclaimed “republics” in Ukraine. While these “republics” are illegal, questions of their legitimacy are commonly discussed almost entirely through Weberian rule-conformity. We argue that this one-dimensional view of legitimacy overlooks the rich context of normative aspects of power relationships. If the occupied Donbas is to be reintegrated into Ukraine, it is essential to understand the perceived legitimation of the political institutions in this region. We use David Beetham’s framework of legitimacy—consisting of legality, morality, and consent—to analyze the “republics’” pursuit of legitimacy. Our analysis leads to the proposition that while the “republics” are illegal, their supporters’ normative perceptions of the right to govern have ascribed more validity to the fake “governments” than what would have been expected from a legal point of view. Additionally, while a ceasefire between the Russian proxies and Ukraine’s forces has reduced violence, it has also levied temporal effect on the legitimation of illegitimate institutions. Our treatment of the process of legitimation over time helps us identify potential strategies of delegitimization should DPR and LPR reincorporate with Ukraine-controlled territory. Without dismantling internal perceptions of institutional legitimacy among inhabitants of nongovernment-controlled areas, a re-integration could not be accomplished.
Keywords: Russia; Ukraine; conflict management; de facto states; dept.soc; institutional framework; legislation; legitimacy; peer-reviewed; political conflict; political power; reconciliation; secessionism; separatism

Understanding the potential of state-based public health genomics programs to mitigate disparities in access to clinical genetic services - Senier, Laura; Tan, Catherine; Smollin, Leandra; Lee, Rachael (Genetics in Medicine, 2019)
Keywords: dept.soc; peer-reviewed